Succession in salt marshes – large‐scale and long‐term patterns after abandonment of grazing and drainage. Issue 1 (19th August 2014) - Rupprecht, Franziska; Wanner, Antonia; Stock, Martin; Jensen, Kai; Middleton, Beth
Abstract Questions In the early 1990s, grazing and drainage have been abandoned in many artificially created mainland salt marshes of the Wadden Sea to increase their natural character and heterogeneity of vegetation composition. We asked: how did vegetation succession in the low and high marsh respond to this change in management from a large‐scale and long‐term perspective, and what were the major drivers of successional change? Location Wadden Sea coast, Schleswig‐Holstein, Germany. Methods We used vegetation data from the Trilateral Monitoring and Assessment Program (TMAP) for around half of the Wadden Sea mainland salt marshes to identify main successional pathways of the TMAP vegetation types Puccinellia maritima and Festuca rubra, dominating low and high marsh areas, respectively, prior to the change in management. Drivers of succession were analysed using classification and regression tree models, a non‐parametric vegetation modelling technique. Results Since the abandonment of grazing and drainage, progressive succession towards the TMAP vegetation types Atriplex portulacoides and Elymus athericus strongly increased and mostly occurred in abandoned areas at medium to high elevation. Retarded and retrogressive succession decreased and mostly occurred in grazed and low‐lying areas. Persistance of the early successional vegetation type Puccinellia maritima in the salt marshes of the northern Wadden Sea suggests that large‐scale gradients of salinity, inundation frequency and sedimentation lead to geographical variation in the pace of succession. Conlusions Considered from a large‐scale and long‐term perspective, abandonmnent of grazing and drainage caused spread of grazing‐sensitive plant species from mid‐ and late‐successional stages. This change in vegetation composition affects species diversity and ecosystem functions of the Wadden Sea mainland salt marshes. Grazing regime and elevation were found to be the most important drivers of succession. To achieve and maintain large‐scale heterogeneity in vegetation composition, we recommend management to maintain a mosaic of grazed and ungrazed areas, and to consider the role of large‐scale gradients of environmental factors driving succession.